PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN LITERASI MATEMATIS PESERTA DIDIK KELAS VIII - ., Nursifah (Departemen Matematika, 2023)
Mathematical literacy is the. ability to apply mathematics in everyday life. Mathematical literacy is an important skill that students must have to solve everyday problems and develop their math skills. In fact, the mathematical literacy of grade VIII students.i of SMP Negeri 25 Padang is still low. Mathematical literacy skills can be improved, for example with the Problem-Based Learning model. The purpose of this study was to find out whether the mathematical literacy abilities of studentsi who were taught using a problem-basedrn learning model were better. than those taught with conventional models in Class VIII SMP Negeri 25 Padang. The nature of this research is descriptive research and quasiexperimental with a non-equivalent control group which is carried out by post-test only. The rnpopulation of this study were studentsi of class VIII SMP Negeri 25 Padang with. samples from class VIII-4 and VIII-7. The. instrumentrn used in this study was a description-based mathematicali literacy test. Keywords – Mathematical literacy ability, Problem Based Learning, Conventional Learning